Mechanisms of angiogenesis in tumour - Zhang, Run; Yao, Yutong; Gao, Hanwei; Hu, Xin (Frontiers in Oncology, 2024)
Angiogenesis is essential for tumor growth and metastasis. Antiangiogenic factor-targeting drugs have been approved as first line agents in a variety of oncology treatments. Clinical drugs frequently target the VEGF signaling pathway during sprouting angiogenesis. However, due to the toxic side effects of antiangiogenic drugs and the enhancement of tumor resistance to them, clinical treatment failure has occurred frequently. Accumulating evidence suggests that tumors can evade antiangiogenic therapy through other angiogenesis mechanisms in addition to the vascular sprouting mechanism involving endothelial cells. These mechanisms include (1) sprouting angiogenesis, (2) vasculogenic mimicry, (3) vessel intussusception, (4) vascular co-option, (5) cancer stem cell-derived angiogenesis, and ( 6) bone marrow-derived angiogenesis. Other non-sprouting angiogenic mechanisms are not entirely dependent on the VEGF signaling pathway. In clinical practice, the conversion of vascular mechanisms is closely related to the enhancement of tumor drug resistance, which often leads to clinical treatment failure. This article summarizes recent studies on six processes of tumor angiogenesis and providesoffers suggestions for developing on how to create more effective techniques to improve the efficacy of antiangiogenic treatment.